Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content1. A training program based on the SWOM model, in developing creative teaching skills with students of the Islamic Studies Curriculum Department at the College of Education, Sana’aDr. Abdul-Rahman Qaid Abdullah Al-Yusufi, Prof. Abdul-Salam Abdo Qasim Al-Mekhlafi2. The Reality of Using Blended Learning in the Arab East Colleges  from the Point of View of Faculty MembersMs. Mahasin Hussain Theqah, Co-Prof. Dalia Nabil Al-Manhrawi3. Teaching of Non- Linguistic Disciplines (NLD) in Secondary school in Morocco: Reference, organizational, pedagogical and procedural requirements towards improving learningAccredited Lecturer \ Youssef EL GUAMRI, Accredited Lecturer \ Omar AMAHMID, Associate Professor \ Youness RAKIBI, Associate Professor \ Abdelhalim FAKIHANI, Accredited Lecturer \ Mohamed YAZIDI, Accredited Lecturer \ Bouchra RAZOKI, Accredited Lecturer \ Khaidija KAID RASSOU, Lecturer \ Saadia OUIZAT , Accredited Lecturer \ Ouafae SERRAR4. The Extent of Future Thinking Skills Inclusion in Digital Skills Course  for the Fourth Grade of Elementary Schools in the Kingdom of Saudi ArabiaMs. Amani Muneer Alnufaei, Prof. Najwa Atyan Almohammadi5. The Impact of Project-Based Learning Using a STEM Approach on Developing Entrepreneurship Skills Among High School Female Students in Digital Technology (2-2)Ms. Nuriyyah Naser Adullah Almoafa6. Reasons for Weak Reading Skills in English among Elementary School Students from the Perspective of English Teachers in Elementary Schools in RiyadhMs. Shamma Sulimsn Aljurijeer7. The effectiveness of training fourth grade students on mental arithmetic strategies in improving their performance in finding the results of arithmetic operations on numbersMs. Anwaar Sulaiman Ali Al-Maqbali, Ms. Hamida Hamid Khalfan Al-Mufarji
Keywords: Journal of Curriculum and Teaching Methodology